2015
DOI: 10.1177/0284185115600916
|View full text |Cite
|
Sign up to set email alerts
|

Administration of unfractionated heparin with prolonged fasting could reduce physiological 18F-fluorodeoxyglucose uptake in the heart

Abstract: Background: The physiological uptake of F-18 fluorodeoxyglucose (FDG) in the heart often

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…Furthermore, one study showed that despite undergoing an 18-h fast, 38% of individuals still demonstrated physiologic 18 F-FDG uptake, necessitating additional measures. 54 …”
Section: Prolonged Fastingmentioning
confidence: 99%
“…Furthermore, one study showed that despite undergoing an 18-h fast, 38% of individuals still demonstrated physiologic 18 F-FDG uptake, necessitating additional measures. 54 …”
Section: Prolonged Fastingmentioning
confidence: 99%
“…Although the reduction in physiologic uptake is significantly greater after more than 18 h of fasting than after a shorter fast, patient compliance with the longer fast can be challenging. Furthermore, one study showed that despite undergoing an 18-h fast, 38% of individuals still demonstrated physiologic 18 F-FDG uptake, necessitating additional measures (54).…”
Section: Prolonged Fastingmentioning
confidence: 99%
“…Kobayashi et al reported that carbohydrate restriction (<10 g of carbohydrate) for 24 hours or more with a low-carbohydrate, high-fat diet more effectively suppressed physiological FDG uptake compared with a fasting only protocol (15). Intravenous injection of unfractionated heparin combined with extended fasting is also reported to be effective in suppressing physiological FDG uptake (16,17). Unfractionated heparin increases serum free fatty acid, which suppresses myocardial glucose metabolism (18).…”
Section: Patient Preparation For Fdg Pet Acquisitionmentioning
confidence: 99%